1986
DOI: 10.1161/01.str.17.5.865
|View full text |Cite
|
Sign up to set email alerts
|

The association of hyperglycemia with cerebral edema in stroke.

Abstract: SUMMARY A retrospective review of stroke patients admitted to our hospital revealed 39 patients diagnosed as suffering an acute completed ischemic stroke who also had had fasting (AC) serum glucose determinations and sequential computer tomography (CT) studies. The patients were divided into three groups on the basis of mean AC serum glucose: Group 1 (n = 12) mean serum AC glucose > 150 mg/dl; Group 2 (n = 13) mean serum AC glucose 100-150 mg/dl; and Group 3 (n = 14) mean serum AC glucose < 100 mg/dl.CT scans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
3
3

Year Published

1988
1988
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(84 citation statements)
references
References 32 publications
1
76
3
3
Order By: Relevance
“…[74][75][76][77][78][79][80][81][82] However, HG may not be associated with poor outcome in patients with lacunar stroke. [82][83][84] The association between HG and poor clinical outcome is more pronounced in patients treated with thrombolytic therapy than in patients not treated with tPA.…”
Section: Glycemic Management During Endovascular Treatment Of Aismentioning
confidence: 99%
“…[74][75][76][77][78][79][80][81][82] However, HG may not be associated with poor outcome in patients with lacunar stroke. [82][83][84] The association between HG and poor clinical outcome is more pronounced in patients treated with thrombolytic therapy than in patients not treated with tPA.…”
Section: Glycemic Management During Endovascular Treatment Of Aismentioning
confidence: 99%
“…Baseline blood glucose was an independent predictor for CED development in our study, including severe edema, as was indicated but not statistically significantly associated in some earlier studies. 12,28,29 One explanation for this may be an impaired blood-brain barrier caused by high levels of glucose. 30 Level of consciousness has been found to be an independent predictor of all types of CED.…”
Section: 23mentioning
confidence: 99%
“…This implies that some neurons require an increased capacity for glucose uptake over an extended period of time (1-4 h) to survive the energy crisis created during glutamate excitation. Interestingly, hyperglycemic conditions during reperfusion after both transient and focal ischemia have been shown to significantly increase infarct size and neuronal injury in vivo (Berger and Hakim, 1986;Nedergaard, 1987). Therefore, it may be the case that many neurons within the penumbra region of an infarct have an increased capacity for glucose uptake for a number of hours after an ischemic event (Vannucci et al, 1996(Vannucci et al, , 1998.…”
Section: Glut3 Translocation and Neuronal Viabilitymentioning
confidence: 99%